Eksplorasi Eksistensialisme dalam Cerita Pendek “Al-Jahim Laisa Fihi Mir’ah” dan Teks Drama “No Exit” - Kumalasari; Tatik Mariyatut Tasnimah; Bihevi Alfain (Madah: Jurnal Bahasa dan Sastra, 2025)
This research aims to explain and compare the form of existentialism contained in the short story “Al-Jahim Laisa Fihi Mir'ah” by Ihsan Abdul Quddus and the drama text No Exit by Jean Paul Sartre. This type of research is descriptive qualitative research using the reading and note-taking method. The data collection technique is carried out using the comparative literature approach which assumes that the similarity of the two works above is due to influence factors. This research found some similarities and differences between the two works. Forms of existentialism that are similar in both include: alienation, existence precedes essence, the impact of one's existence on others, and freedom and responsibility. The similarities prove that there is an influence of the short story “Al-Jahim Laisa Fihi Mir'ah” from the drama text No Exit.